Experimental approach to the prophylaxis and treatment of acute lung injury syndrome with proteinase inhibitors and corvitin - Moĭbenko, O O; Kubyshkin, A V; Kharchenko, V Z; Horokhova, N Iu; Semenets', P F (Fiziolohichnyi zhurnal (Kiev, Ukraine : 1994), 2003)
The results of a combined study of the proteolysis on a model of post-ischemic toxemia in rats showed a decrease in antiproteinase potential and an activation of proteolysis. The activation of proteolysis and inhibition of antiproteinases was observed not only in the blood, but also in the bronchoalveolar secretion. Those changes were accompanied with the changes in the morphological structure of the lungs. The data obtained have shown a high effectiveness of proteinase inhibitor (contrical) and an antioxidant of flavonoid group (corvetine). Those drugs decreased the morphological changes in the lungs and prevented the development of imbalance in proteinase-inhibitor system. The prophylactic effect was more considerable when both drugs were used in a combined way.